A study of innovation barriers and the resulting strategic options in the brazilian industry - Lima, Mateus José do Rêgo Ferreira (2018)
Innovation has been acknowledged as a main driver for competitiveness whether it is for a firm, industry, region or country. Solutions for improvements in products and processes have emerged from the multitude of innovation tools and its techno-scientific features. However, the path traced by firms to innovate is rarely clear and not always successful. In this regard, a variety of uncertainties have been shaped into the obstacles that hinder firm’s innovation activities and prevent them to innovate. To the best of our knowledge, there is no literature that directly addresses the obstacles for innovation in Brazil in a broader sense. Also, the articles focused on the strategies of innovation did not investigated its antecedents, characterizing a clear avenue for research. The objective of this study is to understand which innovation barriers affect the Brazilian industry and how they influence the adoption of innovation strategies. In this way, one of the main strategies that stand out in literature is industrial cooperation. Secondly, a discussion that stands out in literature regards the existence of two juxtaposed strategies, known as Market-orientation and Technology-acquisition. This work combined with an exploration of the current state of industrial innovation studies in Brazil through a systematic review. Also, we combined multiple methods to quantitatively analyze the relationship among variables of the Brazilian innovation survey (PINTEC). The main results of this dissertation are: (i) the systematization of the industrial innovation literature in Brazil and the proposition of a research agenda; (ii) the assessment of which innovation barriers trigger or which affect industrial cooperation for R&D; (iii) the exploration of the innovation barriers’ role on the choice of firms to adopt either Market-orientation or Technology-acquisition as innovation strategies. From an academic perspective, this study contributes to clarify future avenues of research on industrial innovation in Brazil and to provide insights about the role of innovation barriers in the Brazilian industry. From a practical point of view, this manuscript presents a map of findings so as industries can use in a strategic way. Also, we bring insights on how innovation strategies should be adopted in relation to innovation barriers.